Rye plant parameters in the Westsik crop rotation experiment - Hadházy, Ágnes; Abido, Waleed A.E.; Aranyos, Tibor József; Demeter, Ibolya; Henzsel, István (Acta Agraria Debreceniensis, 2020)
Our research work was carried out in the Westsik crop rotation field experiment in 2018. The main research purpose was to analyse the effect of the different organic and chemical fertilizers on parameters of rye. Our results revealed some differences between the different fertilization methods. One spike weight, grain weight of one spike, rye plant height, rye plant weight per m2 and 1000 seed weight in crop rotations VII, XV and VIII were different from the data of all crop rotations. This finding can be explained by the fact that crop rotations VII and XV were non-fertilized, only 23.3 t ha-1 straw manure (VII) or green lupine manure was applied as a second crop (XV). In addition, crop rotation VIII consists of four parts where we apply chemical fertilization with green lupine manure as a main and second crop. There is a positive close correlation between rye plant height and other studied characters (rye plant weight per m2, spike length, weight of one spike, grain weight per spike, spike weight per m2, grain weight per m2 and 1000 seed weight).